2021
DOI: 10.1038/s41598-021-91434-6
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and molecular milieus of ovarian follicles are diversely affected by human chorionic gonadotropin and gonadotropin-releasing hormone in prepubertal and mature gilts

Abstract: Different strategies are used to meet optimal reproductive performance or manage reproductive health. Although exogenous human chorionic gonadotropin (hCG) and gonadotropin-releasing hormone (GnRH) agonists (A) are commonly used to trigger ovulation in estrous cycle synchronization, little is known about their effect on the ovarian follicle. Here, we explored whether hCG- and GnRH-A-induced native luteinizing hormone (LH) can affect the endocrine and molecular milieus of ovarian preovulatory follicles in pigs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 69 publications
2
16
0
Order By: Relevance
“…It is thought that CYP17A1, the last enzyme in the biosynthesis of androgens, becomes the rate-limiting enzyme of follicular estrogen synthesis in pigs [ 22 ]. Furthermore, our recent results and previous studies [ 13 , 14 ] confirmed the hypothesis that the availability of substrate, but not the magnitude of CYP19A1 mRNA/protein expression, is critical for maintaining E2 synthesis in the porcine preovulatory follicle.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…It is thought that CYP17A1, the last enzyme in the biosynthesis of androgens, becomes the rate-limiting enzyme of follicular estrogen synthesis in pigs [ 22 ]. Furthermore, our recent results and previous studies [ 13 , 14 ] confirmed the hypothesis that the availability of substrate, but not the magnitude of CYP19A1 mRNA/protein expression, is critical for maintaining E2 synthesis in the porcine preovulatory follicle.…”
Section: Discussionsupporting
confidence: 87%
“…In conclusion, this study, together with our two already published studies [ 13 , 14 ], indicates that sexual maturity, altrenogest and exogenous gonadotropins significantly affect endocrine and molecular regulators of ovarian follicle development and function in gilts. Whereas the diversity of hCG and LH (released by delivered GnRH) action was presented in detail by Ziecik and co-workers (2021), this study compared eCG- and hFSH-priming effects in gilts.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations